2019
DOI: 10.1111/dom.13924
|View full text |Cite
|
Sign up to set email alerts
|

Incretin‐based glucose‐lowering medications and the risk of acute pancreatitis and malignancies: a meta‐analysis based on cardiovascular outcomes trials

Abstract: Some epidemiological data have suggested an elevated risk of acute pancreatitis and pancreatic cancer after exposure to glucagon‐like peptide (GLP)‐1 receptor agonists and dipeptidyl peptidase (DPP)‐4 inhibitors. Recently, such outcomes have been assessed and adjudicated as adverse events of special interest in cardiovascular outcomes studies. We performed a meta‐analysis of cases of acute pancreatitis and pancreatic cancer as well as any malignant neoplasm reported in cardiovascular outcomes trials (CVOTs) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(58 citation statements)
references
References 31 publications
2
51
3
2
Order By: Relevance
“…Others have reported an increased protein synthesis rather than DNA synthesis to be responsible for enlargement of the pancreas 18 . Chronic administration of GLP‐1 in mice, rats and monkeys did not induce any structural changes (neoplasia or signs of inflammation) of the pancreatic tissue, 19 in line with the recent meta‐analyses from the cardiovascular outcome trials which, as mentioned, did not show differences in the incidence of pancreatitis or pancreatic cancer between subjects treated with GLP‐1RAs or placebo 11 . The effects of the GLP‐1RA liraglutide on pancreas volume, oedema and DNA synthesis have, to our knowledge, not been investigated in humans.…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…Others have reported an increased protein synthesis rather than DNA synthesis to be responsible for enlargement of the pancreas 18 . Chronic administration of GLP‐1 in mice, rats and monkeys did not induce any structural changes (neoplasia or signs of inflammation) of the pancreatic tissue, 19 in line with the recent meta‐analyses from the cardiovascular outcome trials which, as mentioned, did not show differences in the incidence of pancreatitis or pancreatic cancer between subjects treated with GLP‐1RAs or placebo 11 . The effects of the GLP‐1RA liraglutide on pancreas volume, oedema and DNA synthesis have, to our knowledge, not been investigated in humans.…”
Section: Introductionsupporting
confidence: 81%
“…Initially, there was fear that the rises were signs of pancreatitis 9 . However, an association between the use of GLR‐1RAs and incidence of acute pancreatitis or pancreatic cancer has not been confirmed, neither in preclinical safety studies nor in the large, long‐duration cardiovascular outcome trials with GLP‐1RAs 2,9–12 …”
Section: Introductionmentioning
confidence: 99%
“…However, rather than the main cause leading to T2DM, the deficiency of incretin was more often considered as a results of deteriorating glucose homeostasis in T2DM ( Knop et al, 2007b ; Knop, 2010 ). Incretin-based pharmacotherapy has been suggested to be correlated with increased risk of AP in T2DM patients ( Azoulay et al, 2016 ; Ueberberg et al, 2016 ; Tseng et al, 2017 ) although more recent and thorough studies have suggested that incretin-based treatment does not increase pancreatitis risk ( Wang et al, 2015 , 2018 ; Abd El Aziz et al, 2020 ). The GLP-1 receptor may activate PSCs, changes pancreatic gene, and enhances pancreatic mass, therefore inducing pancreatic injury ( Koehler et al, 2009 ; Yang et al, 2013 ).…”
Section: Incretin: Gut-islet Hormone Interactionmentioning
confidence: 99%
“…Due to potential differences in symptoms and etiology between DMs, personalized hyperglycemia solutions should pay special attention to drug indications and contraindications. For example, although being preferred selections for DM treatment in many situations, incretin-based therapies such as glucagon-like peptide-1 (GLP-1) receptor agonists have been suggested to be associated with increased pancreatitis risk ( Buse et al, 2017 ; Abd El Aziz et al, 2020 ). Although more thorough studies have suggested that incretin-based treatment did not increase pancreatitis risk ( Wang et al, 2015 , 2018 ; Abd El Aziz et al, 2020 ), it is still suggested to be used with vigilance ( Buse et al, 2017 ; Abd El Aziz et al, 2020 ).…”
Section: Introduction: Clinical Features Of Depmentioning
confidence: 99%
“…Unfortunately, in the majority of studies these have been assessed by participant self-report which is known to be unreliable (118) iii) the insulinotropic actions of GLP-1-based therapy necessitates adequate endogenous insulin secretory capacity iv) GLP-1 agonists are contraindicated in the rare case of medullary thyroid carcinoma. While recent observational studies and meta-analyses have failed to establish a causal relationship between GLP-1 agonists and acute pancreatitis, this remains potential issue (94,119). A post-hoc analysis of the LEADER trial showed that the GLP-1 receptor agonist, liraglutide, to have an increased risk of gallbladder or biliary tract related events compared with placebo (120).…”
Section: Glp-1 Receptor Agonistsmentioning
confidence: 99%